PERANAN GOOD CORPORATE GOVERNANCE DAN DIMODERASIKAN DENGAN ARUS KAS TERHADAP FINANCIAL DISTRESS - Muhamad Alif Ilmadia Purnomo (2021)
This study aims to analyze the effect of the implementation of god corporate governance (GCG) which consist of the size of board directors, independent commissioners, and audit committees and if moderated by cash flow on the level of financial distress in the listed non banking financial sector companies on the Indonesia Stock Exchange on period 2017-2019. This study uses a quantitative approach with secondary data sources taken from financial statements and annual reports. The sample used for this research is 49 companies with a total 147 observations based on purposive sampling. The data analysis technique uses the Longitudinal Ordered Probit Regression, namely probit regression consisting more than two categories on dependent variable and combined with panel data. The result showed that independent variable size of board directors and moderating variable audit committee with cash flow had an effect on financial distress. Menawhile, the independent commissioners variable, audit committee, moderating variable of board directos with cash flow, and moderating variable of independent commissioners with cash flow have no effect on financial distress. Control variable, leverage has an effect on financial distress. Keywords: Size of Board Directors, Independent Commissioners, Audit Committee, Cash Flow, Leverage, and Financial Distress.